The Microsoft Crabby Office Lady tells it like it is : secrets to surviving office life - Stahl, Annik (Microsoft Press, 2006)
The Crabby Office Lady's humorous online column reaches more than 250,000 people a month, and more than 10,000 people view her videos each month. The real Crabby Office Lady, Annik Stahl, has helped Microsoft put a human face on the sometimes frustrating world of work. In this humorous but practical take on how to survive today's office environment, Microsoft's very own Crabby Office Lady shows you how to make the most of Microsoft® Office programs so that you can be more efficient, collaborate more effectively, and spend more time doing the things that really matter to you. Topics include: {u2022} Minding your e-mail manners {u2022} Customizing Office: toolbars, menus, colors, buttons, fonts, templates, and more {u2022} Working with difficult people, collaborating, and surviving office life and culture {u2022} Using the "get away from it all" checklist to prepare for vacation, so that you don't come back to an avalanche of work {u2022} Surviving performance reviews: how to track projects, make notes, and keep track of wins and losses on a daily (or weekly) basis, rather than trying to pull it together at the end of the year {u2022} Improving ergonomics and using the accessibility features in Office and Microsoft Windows® {u2022} Demystifying computer terms, e-mail terms, and general software terms {u2022} Working from home: pros, cons, and best practices for telecommuting {u2022} Delegating and preparing for effective meetings {u2022} Taking advantage of Office Online templates, clip art, training, and the Office Marketplace.